Strategi Pembelajaran Al-Qur’an dalam Meningkatkan Kualitas Bacaan Al-Qur’an Santri di Pondok Pesantren Fathul Hidayah Lamongan - Nukh Khozain; M. Farich Al-Ayubi (LPPM STIT Miftahul Ulum Bangkalan, 2021)
In simple terms, learning strategies can be interpreted as tactics or outlines of directions used by teachers in the teaching and learning process in order to influence students (santri) so that learning goals and objectives are achieved. The strategy must consist of steps that are arranged in a planned and systematic manner using certain methods and techniques. The use of strategies in learning is intended so that the lesson can be captured, understood and used by students properly, because in that way maximum results will be achieved in learning. The type of research used is a type of qualitative research. In the course of collecting data, researchers used the methods of documentation, observation and interviews. As for the analysis, the researcher uses descriptive qualitative analysis techniques, namely describing and interpreting the data that has been obtained. The results of this study indicate that the Al-Qur'an learning strategy in improving the quality of reading the Qur'an of students at the Fathul Hidayah Pangean Islamic Boarding School shows that it is implemented well, because it is supported by several supporting factors, especially by the caregiver figure of the Fathul Hidayah Pangean Islamic Boarding School. who are experts in the field of learning the Qur'an, educational programs that have been implemented since this pesantren was founded, experienced teachers and student’s enthusiasm for learning, and a conducive environment.